Integrated Weed Management in Upland Rice - Shyam Nair S (Department of Agronomy, College of Agriculture, 2001)
A field experiment was conducted at the Instructional Farm, College of Agriculture, Vellayani, Thiruvananthapuram to evolve a suitable integrated weed management practice for upland rice. The study was conducted during the virippu season of 1999. The field experiment was laid out in split plot design having three replication with three main plot treatments and six subplot treatments. Three different spacings i.e., 15 x 10 cm 15 x 10 cm, 20 x 10 cm and 20 x 15 cm were the main plot treatments. Sub plot treatments were different weed management strategies consisting of three different herbicides in combination with one hand weeding, hand weeding alone twice, unweeded check and weed free check. Pendimethalin, Fluchloralin and Butachlor were the herbicides used in the experiment. The rice variety used for the experiment was Matta Triveni. The results of the study revealed that grasses, broadleaved weeds and sedges competed with the rice crop. Different weed management practices included in this experiment significantly influenced the intensity and distribution of the weeds, but the fluchloralin treatment (W2) resulted in phytotoxicity and affected the crop stand considerably. The application of butachlor + one hand weeding at three weeks after sowing (W3) and pendimethalin + one hand weeding at three weeks after sowing (wj ) showed very high control over weeds throughout the crop growth period. The plots hand weeded twice at 20 and 40 days after sowing also